2022
DOI: 10.1002/art.42133
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐Derived Regenerative Cell Transplantation for the Treatment of Hand Dysfunction in Systemic Sclerosis: A Randomized Clinical Trial

Abstract: Objective Hand dysfunction is common in systemic sclerosis (SSc). We undertook this study to evaluate the capacity of autologous adipose‐derived regenerative cells (ADRCs) to improve hand function in SSc patients. Methods The Scleroderma Treatment with Celution Processed Adipose Derived Regenerative Cells Trial was a prospective, randomized, double‐blind trial of ADRCs, in which ADRCs were obtained from patients with SSc by small‐volume adipose tissue harvest, and the fingers of each patient were injected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The application of decanted fat [ 27 ], centrifuged fat [ 16 ], and the ADSVF [ 10 , 17 , 24 , 34 ], has consistently and significantly improved pain, RP, and the healing of digital ulcers in the hands of patients with SSc, thereby improving their quality of life. Other inconsistently observed benefits, such as decreased digital circumferences, improvements in digital mobility and strength [ 35 ], improvements in the formation of new subungual capillaries, and improvements in function based on Cochin Functional Scale Scores, have also been reported [ 14 , 15 , 23 ]. Though, these previous studies have been uncontrolled with a short follow-up period of 6 months [ 10 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of decanted fat [ 27 ], centrifuged fat [ 16 ], and the ADSVF [ 10 , 17 , 24 , 34 ], has consistently and significantly improved pain, RP, and the healing of digital ulcers in the hands of patients with SSc, thereby improving their quality of life. Other inconsistently observed benefits, such as decreased digital circumferences, improvements in digital mobility and strength [ 35 ], improvements in the formation of new subungual capillaries, and improvements in function based on Cochin Functional Scale Scores, have also been reported [ 14 , 15 , 23 ]. Though, these previous studies have been uncontrolled with a short follow-up period of 6 months [ 10 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several authors reported improved labial rhyme opening through reduced perioral fibrosis and neoproliferation of dermal capillaries [ 108 , 109 , 110 , 111 , 112 ]. More recently, two controlled trials failed to reach the primary endpoint of significant improvement of hand function in SSc patients treated with SVF [ 113 , 114 ]. Larger trials are needed to better understand the therapeutic efficacy of AT-MSCs injection on skin fibrosis of SSc patients.…”
Section: Mesenchymal Stem Cells (Msc)mentioning
confidence: 99%
“…2,3 In recent years, adipose tissue and its derivatives have been commonly used in the clinical treatment of LoS and have achieved good therapeutic effects. [4][5][6][7][8] Structural support and biomolecules provided by autologous fat grafts effectively improved localized scleroderma-related contour irregularities and lipoatrophy. 7 Unfortunately, the high oxygen consumption of mature white adipocytes makes them unable to tolerate an ischemia-hypoxic environment, prone to apoptosis, and release many oily lipid droplets after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the presence of subcutaneous adipose tissue exerts a protective effect against skin fibrosis 2,3 . In recent years, adipose tissue and its derivatives have been commonly used in the clinical treatment of LoS and have achieved good therapeutic effects 4–8 . Structural support and biomolecules provided by autologous fat grafts effectively improved localized scleroderma‐related contour irregularities and lipoatrophy 7 .…”
Section: Introductionmentioning
confidence: 99%